(untitled) (Global Journal of Science Frontier Research, 2012)
In this paper we have established a theorem wherein we have obtained the image of modified H-transform under the pathway fractional integral operator defined by Nair [8]. Three corollaries of the main theorem have been derived. Our findings provide interesting unification and extension of number of (new and known) results.